El Acuerdo Bruselas 2017 para Latinoamérica: una iniciativa de la GARD y SLaai - Gómez, René Maximiliano; González Díaz, Sandra Nora; Urrutia Pereira, Marilyn; Valentín Rostan, Marylin; Yáñez, Anahí; Jares, Edgardo José; Cruz, Álvaro A.; Calderón, Moisés; Bousquet, Jean J.; Latinoamericana de Alergia, Asma, Sociedad; Against Chronic Respirat, Global Alliance (Colegio Mexicano de Inmunología Clínica, 2018)
Abstract The Global Alliance against Chronic Respiratory Diseases (GARD) is a network of organizations coordinated by the World Health Organization. It is a voluntary alliance of national and international organizations, institutions and agencies with global scope that are committed with actions to improve access to prevention, care and essential medications. On its last annual meeting, celebrated in Brussels (Belgium) in September 2017, the need for actions and representation to be grouped by geographic regions was discussed. There are several successful programs regarding morbidity and mortality control of these diseases, and others that improve cost-beneﬁ t and quality of life. Thus, SLaai proposes to contribute to the diﬀ usion and knowledge of chronic respiratory diseases magnitude and risk factors, to identify successful programs in Latin America in order for them to be replicated in the region and to generate strategic alliances for the strengthening of joint actions.